Effect of Characteristic Parameters and Distribution of Friction Pair Surface Texture on Lubrication Properties - Haowen Qiang; Guangming Gao; Sitong Ye; Linkai Cheng; Quandai Wang (Lubricants, 2023)
Based on the basic mechanism and bionics principle that texture affects the dynamic pressure effect of lubricating medium, a V-shaped texture that converges along the sliding direction is designed. Through numerical simulation, the optimal geometric parameters and distribution of the V-shaped and textures are obtained. A textured surface with various texture features is prepared using a nanosecond ultraviolet laser with bearing steel as substrate. Tribological experiments with friction and wear tester are performed to investigate the effect of characteristic parameters and distribution of surface texture on the lubrication performance and the lubrication properties are compared and analyzed with that of circular texture. Hence, this investigation provides a research direction to improve the lubrication performance between frictional pairs under fluid lubrication condition to reduce the frictional wear of mechanical systems. The results show that under the conditions of optimal parameters, due to the effect of convergence and extrusion on the flow of lubrication medium, the V-shape texture is better than the circular texture in improving the lubrication performance. The optimal characteristic parameters of V-shape texture are: 60° for the angle between the two wings, 0.53 for shape parameter, 25.9% for area ratio, 13 μm depth, 60% texture area coverage ratio, and the inlet of flow field of the texture distribution position.